Native and introduced forage cacti in Saanen dairy goat diets - Góes Neto, Pedro Etelvino de; Silva, José Geraldo Medeiros da; Aguiar, Emerson Moreira de; Melo, Airon Aparecido Silva de; Lima, Guilherme Ferreira da Costa; Cardoso, Daniel Barros; Silva, Hildelblano Pereira da (Acta Scientiarum. Animal Sciences, 2020)
This study aimed to assess the nutrient intake and milk production of dairy goats fed with total mixed rations with different species of forage cacti. Five pluriparous Saanen goats (50 ± 4 kg) at nine weeks of lactation were allocated in a Latin square (5 x 5) with five diets and five periods. Each period was composed of 10 days for adaptation and seven days for collection. The treatments were composed of 473.0 to 501.0 g kg-1 of forage cacti: xiquexique (Pilosocereus gounellei), mandacaru (Cereus jamacaru), facheiro (Pilosocereus chrysostele), cactus cladodes cv. miúda (Nopalea cochenillifera Salm-Dyck) and cactus cladodes cv. orelha de elefante mexicana (Opuntia stricta); plus sabiá hay (Mimosa caesalpiniifolia) (188.0 to 198.0 g kg-1) and concentrate (311.0 to 329.0 g kg-1). The intake of dry matter, organic matter, ether extract, neutral detergent fiber, total carbohydrates, and water intake through diet components were unaffected by experimental diets. For milk production and feed efficiency, no difference was observed among the diets. All diets containing different species of forage cacti can be used for dairy goats feed.